The Blood Glucose Level of Prolanis Participants in Temanggung Health Center - Sapto Haryatmo; Suci Artanti; Anita Shinta Kusuma (GLOBAL HEALTH SCIENCE GROUP, 2025)
Diabtetes is a chronic disease that occurs due to inadequate control of blood glucose levels when the pancreas dose not produce enough insulin or when the body cannot use the insulin produce effectively, resulting in hyperglicemia. Program pengelolaan Penyakit kronis (Prolanis) is a Chronic Disease Management Program from BPJS Kesehatan that aims to improve the quality of life of patients in order to maintain health for BPJS Kesehatan Participants who suffer from chronic diseases to archieve optimal quality of life with effective and efficient health service Objective: This study aims to determine the description of blood glucose levels in Prolanis participants suffering from Diabetes Mellitus in the Temanggung Health Center. Method: This study uses a quantitative method with a descriptive analytical research design. Results: Most participants do not routinely attend prolanis activities. There is no difference in the average blood glucose levels of participants who routinely and do not routinely attend prolanis activities. Conclusions: The average blood glucose levels of prolanis participants who routinely participate in prolanis activities are not much different from participants who do not routinely participate in prolanis activities. However, when viewed from the minimum and maximum values, the blood glucose levels of prolanis participants who routinely participate in prolanis activities tend to be more stable.